Remarks on Petrascula bugesiaca Bernier, 1979 from the uppermost Jurassic−lowermost Cretaceous limestones of Romania. (8th March 2017) - Bucur, Ioan I.; Săsăran, Emanoil; Pascariu, Lucian
Abstract: Petrascula bugesiaca was described by Bernier (1979) from Portlandian (= Tithonian) limestones of the Sothern Jura Mountains (French Switzerland), and since the first description, has never been identified in any other place. The study of uppermost Jurassic olistoliths embedded in Cretaceous conglomerates from Piatra Craiului (South Carpathians, Romania) gave us the possibility to identify well preserved specimens of this dasycladalean alga. The new material confirms Bernier's ascription of the species to the genus Petrascula, being characterized by a club‐shaped morphology. Abstract : Well preserved specimens of Petrascula bugesiaca Bernier, 1979 identified in Piatra Craiului (Southern Carpathians, Romania) allow a better description of this dasycladalean fossil alga